Thyroid-associated ophthalmopathy and ferroptosis: a review of pathological mechanisms and therapeutic strategies - Ma, Chao; Li, Haoyu; Lu, Shuwen; Li, Xian (Frontiers in Immunology, 2024)
Thyroid-associated ophthalmopathy (TAO) is an inflammatory orbital disease associated with autoimmune thyroid disorders. Owing to the ambiguous nature of the pathogenesis, contemporary pharmacological treatment strategies predominantly involve the use of glucocorticoids and immunosuppressants. However, the adverse effects associated with these agents in clinical practice necessitate further investigation into the disease’s pathogenesis and the identification of novel therapeutic targets and pharmacological interventions. Recent studies suggest that ferroptosis, a novel form of regulated cell death, may play a role in TAO pathogenesis. This review aims to explore the involvement of ferroptosis in TAO and evaluate its potential as a therapeutic target. Key topics include the epidemiology, clinical manifestations, and pathophysiology of TAO, along with the molecular mechanisms of ferroptosis. Evidence supporting ferroptosis in TAO and the therapeutic implications of targeting this pathway are also discussed, alongside challenges and future directions in this emerging research area.